Invasive Alien Plant Species of Grizzled Squirrel Wildlife Sanctuary, Srivilliputhur, Tamil Nadu, India - Priyadharshana, M.; Vadivel, V. (Indian Forester, 2024)
A species that is not native to the ecosystem and whose introduction is predicted to impair animal and human health as well as the environment is known as an invasive species. The goal of the current study is to catalogue the invasive flora in the Srivilliputhur Grizzled Squirrel Wildlife Sanctuary (GSWS), which is under threat from the invasion of alien plant species. From January 2020 to December 2021, extensive field surveys were conducted in the GSWS to identify invasive plant species from various habitats. Observations on-field attributes, including habit, habitat, spread, and significant qualities linked to invasiveness, were made during the repeated field trips. There are 48 recorded invasive plant species in all, spanning 26 families. Most of these species are indigenous to the continent of America. In the investigated geographic area, Asteraceae and Caesalpiniaceae are the two most dominant families of invasive plants. Twenty of these 48 plant species were utilised in different ways by the local tribe in this study area. The results of this study may help to the preservation of biodiversity in the areas that are home to Indian elephants, grizzled squirrels, and other species.